Конституційно-правові засади локальної нормотворчості - Бальций Юрій Юрійович; Бальций Юрий Юрьевич; Bal'cij Jurij (My University, 2011)
The article explores some problems of establishing a local rulemaking in Ukraine. Disclosed the subject of a lo-cal rule-making which includes the organization of the organs and offi-cials of local self-organization of lo-cal referenda, meetings of citizens in the community, the procedure of collec-tive and individual complaints of citi-zens to the bodies and officials of local self-government arrangements for the public (public) hearings , public works, as well as the formation and function-ing of local government, the relation-ship of its elements, their participation in the formulation of municipal policies and the implementation of the func-tions of local government. It is noted that among the acts of local rulemak-ing special place in the statutes of ter-ritorial communities — peculiar acts of their constitution.
Бальций Ю. Конституційно-правові засади локальної нормотворчості / Ю. Бальций // Юридичний вісник. - 2011. - № 3. - С. 45-52.
Keywords: місцеве самоврядування; локальна нормотворчість; статут територіальної громади; конституційно-правові засади; местное самоуправление; локальное нормотворчество; устав териториальной общины; конституционно-правовые основы; local government; local law-making; statutes of territorial communities; constitutional and legal basis